Peran Kelembagaan Kelompok Wanita Tani dalam Peningkatan Kapasitas dan Usaha Pertanian Berbasis Lokal - Edi Usman; Ristiyanti Ahmadul Marunta; Andi Sri Wahyuni Nur; Hariyanti Hariyanti; Sudirman Asis; Bakri Bakri; Muh Ade Ilham Saputra (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This study aims to analyze the institutional effectiveness of Women Farmers Groups (Kelompok Wanita Tani/KWT) in enhancing members’ capacity and their role in agricultural enterprise development in Puulemo Village, Kolaka Regency. A descriptive qualitative approach was employed, with data collected through field observations, in-depth interviews with KWT leaders and members, and a review of relevant secondary data. Data were analyzed inductively through data reduction, data display, and thematic conclusion drawing.The findings indicate that the institutional effectiveness of the KWT is categorized as moderately effective, as reflected in a clear organizational structure, relatively high member participation, and the implementation of various capacity-building activities, including organic fertilizer production, horticultural cultivation, local food processing, and basic marketing practices. These activities have positively contributed to improving members’ knowledge, skills, and economic independence. However, institutional effectiveness has not been fully optimized due to limited post-training assistance, low digital literacy, and inadequate utilization of information technology for business development and product marketing.Furthermore, the KWT plays a strategic role in agricultural enterprise development through production activities, value-added processing, and local-scale marketing, which contribute to increasing household income. This study highlights the importance of strengthening institutional capacity, improving human resources, and optimizing the use of information technology and digital marketing to enhance the sustainability of KWT as a driver of rural women’s economic empowerment and local food security.